Comparing digital libraries with social media from the dual route perspective. Issue 4 (12th August 2019) - Zha, Xianjin; Liu, Kunfeng; Yan, Yalan; Yan, Guanxiang; Guo, Jia; Cao, Fenfang; Wang, Yunzhi
Abstract : Purpose: Digital libraries and social media have emerged as two prominent online information sources with different characteristics. The purpose of this paper is to compare digital libraries and social media from the perspective of the dual route model which outlined a general framework of central and peripheral route-induced attitude change. Design/methodology/approach: Research hypotheses were developed and data collected from users of digital libraries and social media were used for data analysis. The paired samples t -test was employed to compare the means. Findings: Both central route (information quality) and peripheral route (source credibility and reputation) of digital libraries are higher than those of social media. Practical implications: The important status of digital libraries as conventional information sources should be propagated by various "marketing" ways. Managers of digital libraries should encourage their users to use both digital libraries and social media so that some unique advantage of social media could usefully complement digital libraries. They should also recognize the challenge brought by social media and try various ways to enhance reputation. Originality/value: Building on the dual route model, this study compares digital libraries and social media in terms of the central route and peripheral route, which the authors believe presents a new lens for digital library research and practice alike.